2016
DOI: 10.19173/irrodl.v17i3.2203
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Relationship Among the Community of Inquiry Framework, Perceived Learning and Online, and Graduate Students’ Course Grades in Online Synchronous and Asynchronous Courses

Abstract: <p>The Community of Inquiry framework has been widely supported by research to provide a model of online learning that informs the design and implementation of distance learning courses.  However, the relationship between elements of the CoI framework and perceived learning warrants further examination as a predictive model for online graduate student success.  A predictive correlational design and hierarchical multiple regression was used to investigate relationships between community of inquiry factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 37 publications
8
78
1
Order By: Relevance
“…In creating an authentic collaborativeconstructivist learning context, then, the three presences work together and support one another. To wit, social presence has been shown to be the mediating factor between cognitive and teaching presence (deNoyelles, Zydney, & Chen, 2014;Joksimović, Gašević, Kovanović, Riecke, & Hatala, 2015;Whiteside, Dikkers, & Swan, 2017), cognitive presence is most indicative of student satisfaction and success (Holser & Arend, 2012;Yang, Quadir, Chen, & Miao, 2016), and teaching presence is understood to be of the greatest value to students (Hodges & Cowan, 2012;Preisman, 2014) and the most critical in establishing purposeful communities of inquiry (Borokhovski, Bernard, Tamim, Schmid, & Sokolvskaya, 2016;Rockinson-Szapkiw, Wighting, & Nisbet, 2016;Rubin & Fernandes, 2013). As such, Archibald (2013) reported that, in creating communities of inquiry, each of three presences is statistically and conceptually interdependent, and Wicks, Craft, Mason, Gritter, and Bolding (2015), and Rockinson-Szapkiw et al (2016) showed the framework as a whole-through the operationalization of the three presences-to be predictive of learning outcomes.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In creating an authentic collaborativeconstructivist learning context, then, the three presences work together and support one another. To wit, social presence has been shown to be the mediating factor between cognitive and teaching presence (deNoyelles, Zydney, & Chen, 2014;Joksimović, Gašević, Kovanović, Riecke, & Hatala, 2015;Whiteside, Dikkers, & Swan, 2017), cognitive presence is most indicative of student satisfaction and success (Holser & Arend, 2012;Yang, Quadir, Chen, & Miao, 2016), and teaching presence is understood to be of the greatest value to students (Hodges & Cowan, 2012;Preisman, 2014) and the most critical in establishing purposeful communities of inquiry (Borokhovski, Bernard, Tamim, Schmid, & Sokolvskaya, 2016;Rockinson-Szapkiw, Wighting, & Nisbet, 2016;Rubin & Fernandes, 2013). As such, Archibald (2013) reported that, in creating communities of inquiry, each of three presences is statistically and conceptually interdependent, and Wicks, Craft, Mason, Gritter, and Bolding (2015), and Rockinson-Szapkiw et al (2016) showed the framework as a whole-through the operationalization of the three presences-to be predictive of learning outcomes.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Several studies found no relationship with student success in online learning (Aragon & Johnson, 2008;Gibson et al, 2010;Harrell & Bower, 2011;Jost, Rude-Parkins, & Githens, 2012). Some, however, found race combined with other factors yielded a significant association with success (Cochran et al, 2014;Rockinson-Szapkiw, Wendt, Wighting, & Nisbet, 2016;Suphi & Yaratan, 2012).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Evaluating factors of success across multiple class levels in a single study provided a unique and significant contribution that may help to explain some of the contradictions in previous research. Some previous studies, for example, considered targeted populations, such as community college students (Hachey et al, 2014;Jost et al, 2012) or graduate students (Rakap, 2010;Rockinson-Szapkiw et al, 2016). Other studies evaluated a broad population without examining the predictive factors for a given subpopulation (Levy, 2007;Wang et al, 2013).…”
Section: Class Standing and Course Levelmentioning
confidence: 99%
“…Activities associated with teaching presence may have the most direct influence on students' academic achievement (Rockinson-Szapkiw, Wendt, Wighting, & Nisbet, 2016). Instructor activities in an online course account for the most significant impact on student outcomes-higher than student-student interaction and student-content interaction (Marks, Sibley, & Arbaugh, 2005).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Cognitive presence is "the extent to which learners are able to construct and confirm meaning through sustained reflection and discourse in a critical community of inquiry" (Garrison, Anderson, & Archer, 2001, p. 11). The philosophical underpinning of the CoI framework aligns with the social-constructivist view that communication interaction of the teacher, student, and content is essential to learning (Akyol & Garrison, 2011).Activities associated with teaching presence may have the most direct influence on students' academic achievement (Rockinson-Szapkiw, Wendt, Wighting, & Nisbet, 2016). Instructor activities in an online course account for the most significant impact on student outcomes-higher than student-student interaction and student-content interaction (Marks, Sibley, & Arbaugh, 2005).…”
mentioning
confidence: 99%